A Methods engineering study on Metals Engineering Resources Corporation - Acelajado, Carol Anne D.; Balaguer, Aimee O.; Cabreros, Celeste Joy C. (Diliman, Quezon City College of Engineering, 2003)
Metals Engineering Resources Corporation is a manufacturing company that makes automotive parts, sewing machines, transmission parts, glass mold parts, pumps and others, through the green sand process. Among the automotive pars produced are brake discs, drums and front bearings. With over 50 years of foundry experience, METERCOR can consistently produce gray iron castings and automotive gray iron castings. Typical of the company's many satisfied customers are textile firms, engine manufacturers and automotive shops. The methods study is focused on the production process of disc brakes mainly because of the highest contribution of the said product to the company's income. It involves repeated operation which gives the group a lot of opportunity for improvements. Concepts learned in Methods Engineering were applied to generate alternatives to the problems. The operations involved in the production of disc brakes can be divided into two : operations in the foundry and operations in the machine shop. These operations are mixing of sand, core-making, mod making, melting, pouring, harvesting, cleaning and grinding, texture finishing, drilling, surface grinding, balancing and milling, punch marking, dipping, spraying pacing and inspection. However, for the purpose of the study, the production process of disc brakes are followed only from the preparation of the raw materials up to the grinding process (operations in the foundry). This is because of the more manual nature of the tasks involved. Careful analysis of the existing methods were done through the plant visits, interviews and actual observations in order to identify root problems in the operations. Ishikawa diagrams, Streamline Diagnosis Diagrams and other problem solving tools were used to help the group identify the potential problems of the foundry division. The group identified problems in the company's manpower, methods, machines, records and materials. Specifically, the identified problems are no proper compilation of records, manual making of molds, inefficient transfer equipment, lack of proper training, idle machines, non standardized forms no available hard copy and lack of reliable system of worker attendance. Alternatives were generated to solve the said problems. At least three alternatives were generated for each problem area. The group also evaluated these alternatives using value engineering. The nine problem areas are identified. One problem identified is having no proper compilation and arrangement of records, the group suggests the use of labeled envelopes. Employing still a pure manual making of molds was also considered to be a problem, for this to purchase of new semi-automated molding machines is found out to be the best alternative. The company was observed to have inefficient transfer equipment and based on their plant layout and capacity, an installation of wheel conveyor is the best way to respond to this problem. Monitoring of workers while at work is the alternative for the company's lack of proper training for its new workers. Purchasing personal protective equipment for the workers is also recommended. Worn out machines are better repaired first than buy additional if there still is a need. Forms are suggested to be modified and to propose additional forms for some other operations. The group recommends installation of bundy clock to monitor efficiently worker attendance. Lastly, the company is suggested to make brochures and handbooks, to be available. Lastly, the company is suggested to make brochures and handbooks, to be available for immediate transactions, for as of now they employ none. Implementation plans were also provided in case the company would want to use the solutions suggested.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis